Accidents, Liability Obligations and Monopolized Markets for Spare Parts - Pio Baake (The B.E. Journal of Economic Analysis and Policy, 2010)
We analyze the effects of accidents and liability obligations on the incentives of car manufacturers to monopolize the markets for their spare parts. We show that monopolized markets for spare parts lead to inefficiently high prices for spare parts. Furthermore, monopolization induces the manufacturers to choose inefficiently high qualities. The key for these results is the observation that high prices for spare parts entail a negative external effect inasmuch as liability obligations imply that consumers of competing products have to pay the high prices as well.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; aftermarkets; monopolization; liability; Kraftfahrzeugindustrie; Wettbewerb